Diglossia : Formal and Informal Tamil - Ramaswami, N. (My University, 1997)
The present study highlights the differences between Formal Tamil and Informal Tamil at all levels. The phonological differences are discussed in terms of underlying representation, redundancy rules, and phonological rules.
Keywords: English